The Role of Nanoparticles on Topographic Cross‐Talk in Electric Force Microscopy and Magnetic Force Microscopy. Issue 13 (14th January 2020) - Fuhrmann, Marc; Krivcov, Alexander; Musyanovych, Anna; Thoelen, Ronald; Möbius, Hildegard
Abstract : Topographic cross‐talk is still an issue in magnetic force microscopy (MFM) as well as in electric force microscopy (EFM). Using interleave mode measurements, combining a first topographic scan with a second scan in a certain distance from the surface following the topography from the first scan, capacitive coupling effects occur while measuring nanoparticles. This article focuses on the influence of the dielectric constant of polystyrene nanoparticles in interleave mode MFM measurements. To investigate the contribution of the capacitive coupling effect to the signal, nonmagnetic polystyrene nanoparticles are investigated. The tip‐substrate distance change above the nanoparticle leads to a positive phase shift in MFM signals. Simulations and fits to the experimental data allow the investigation of the influence of the dielectric constant of the nanoparticles on topographic effects in interleave mode measurements in general. Abstract : Interleave mode measurements of polystyrene nanoparticles with magnetically coated tips are performed for investigation of topographical crosstalk due to the capacitive coupling effects between conductive tip and substrate system. The influence of the dielectric constant of single seperated polystyrene nanoparticles with a size between 20 and 200 nm is discussed.